2018
DOI: 10.1039/c8dt02999g
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of the novel MOF hcp UiO-66 employing ionic liquids as a linker precursor

Abstract: The novel MOF hcp UiO-66 is synthesized using the ionic liquid ([PBuMEE]2[BDC]) as a linker precursor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
52
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 32 publications
4
52
0
Order By: Relevance
“…These were in good agreement with those typically observed for hcp MOFs. 20,38 The TGA curve showed that the hcp-UiO-66-NaI was stable up to 450 C. The weight loss of 39.6% from 300 to 800 C matched well with the theoretical weight loss of 40.5% based on the conversion of Zr 12 O 15 (BDC) 9 to (ZrO 2 ) 12 (see ESI, Fig. S7 †).…”
Section: Resultssupporting
confidence: 68%
See 2 more Smart Citations
“…These were in good agreement with those typically observed for hcp MOFs. 20,38 The TGA curve showed that the hcp-UiO-66-NaI was stable up to 450 C. The weight loss of 39.6% from 300 to 800 C matched well with the theoretical weight loss of 40.5% based on the conversion of Zr 12 O 15 (BDC) 9 to (ZrO 2 ) 12 (see ESI, Fig. S7 †).…”
Section: Resultssupporting
confidence: 68%
“…Its structure could be viewed as a fusion of two commonly observed Zr 6 clusters. 20,38 A previous study has reported that the formation of hcp structure was due to the low solubility of the ligands in the synthesis media and the presence of large modulators. 38 Therefore, the limited solubilization capacity of the applied SS in combination with the AA rationalized the generation of the hcp phase structure by the developed SSISA strategy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These are named DUT-52, DUT-53 and DUT-84. In addition, it is possible that other structures can be made, for instance, structures with "double clusters" like the ones reported by Cliffe et al 31 and Ermer et al 32 The Zr-BP-4,4 0 -DC lms crystallize to form a small amount of UiO-67 (or a similar phase) and a larger amount of an unknown phase (Fig. 6b).…”
Section: Crystallization and Characterization Of The Lmsmentioning
confidence: 82%
“…When using high amounts HMAc (100 eq) versus ZrCl 4 we identified a change in the structure from the usual UiO-66 facecentered cubic (fcu) 48 to a hexagonal close packed (hcp) structure, which was rarely described in literature after the first observation in 2018. 49 To the best of our knowledge we herein present the first functionalized structure of a hcp UiO-66 MOF. We tested two of the synthesized MOFs in the removal capacities of silver(I) from aqueous solution.…”
Section: Introductionmentioning
confidence: 99%